MOBILISASI DINI DENGAN LATIHAN GERAKAN ROM (RANGE OF MOTION) KEKUATAN OTOT PASIEN PASCA STROKE ISKEMIK DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Harianja, Anita Sari; Susyanti, Deni; Pratama, Muchti Yuda; Jundapri, Kipa; Siregar, Nita Mayrani (LPPM Institut Pendidikan Nusantara Global, 2023)
Ischemic stroke is a condition of hypoxia or decreased oxygenation to brain tissue and is the result of poor blood supply, causing disability. The prevalence of stroke in Indonesia increases at ages > 75 years (50.3%). Objective: This study discusses nursing care for ischemic stroke patients at the Tk II Putri Hijau Kesdam I/BB Medan Hospital, with a focus on two patients who have the same diagnosis but different main complaints. Method: The first patient experienced impaired physical and neuromuscular mobility, with symptoms such as pain on the left side of the body, numbness, weakness, and difficulty sleeping. Meanwhile, other patients experience disorders in different body systems, requiring specific treatment to overcome these complaints. This study emphasizes that appropriate nursing care is needed in treating ischemic stroke patients. Result: Based on the assessment, planning and implementation of nursing actions, this research confirms the importance of correct nursing care in handling Ischemic Stroke at the Tk II Putri Hijau Kesdam I/BB Medan Hospital. This has the potential to increase the understanding and implementation of effective nursing practices for Ischemic Stroke patients.